The challenges for Sweden’s defence and security policies: old and new - Pedone, Luiz (2016)
This article explores Sweden´s defence and security policies in view of old and new geopolitical realities. Extensive document research and interviews were the empirical basis for testing hipotheses: 1) internal politics had little consequence over policies; 2) influence on security through innovative programmes; 3) industrial cooperation and strategic partnerships improved defence industrial base; and 4) contributing to International Security through active participation in UN, NATO and EU peace missions. Both Social-Democratic and Moderate governments have rather shown a great pragmatism. A new public administration was developed in countries emerging from the Soviet sphere. Cooperation and strategic partnerships are now responsible for an increased industrial-technological capacity in Sweden and partners. Increased peace missions participation enlarged international Sweden’s influence. Changing from neutrality to non-alignment better translates the current geopolitical challenges in Northern Europe, Arctic and Baltic regions. These results imply that new security concerns are present and should be considered by policy-makers. Este artículo explora las políticas de defensa y seguridad de Suecia, en vista de las viejas y nuevas realidades geopolíticas. Una amplia investigación de documentos y entrevistas fueron la base empírica para probar algunas hipótesis: 1) la política interna tuve pocas consecuencias sobre las políticas; 2) influencia en la seguridad a través de programas inovadores; 3) la cooperación industrial y asociaciones estratégicas mejoraron la base industrial de defensa; y 4) la contribución a la seguridad internacional a través de la participación activa en la ONU, la OTAN y las misiones de paz de la UE. Ambos gobiernos socialdemócrata y moderado en cambio, han mostrado un gran pragmatismo. Una nueva administración pública se desarrolló en países que salieran de la esfera soviética. Cooperación y alianzas estratégicas son ahora responsables por un aumento de la capacidad industrial-tecnológica ...